Cooking utensil and preparation method thereof
By forming a composite structure of corrosion-resistant layer and non-stick layer on the cooker, the problems of low hardness, wear resistance and environmental pollution of the traditional non-muco film layer are solved, and high thermal conductivity, corrosion resistance, wear resistance and oil storage are achieved. Non-stick effect.
Patent Information
- Application Number
- CN202311059492.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
AI Technical Summary
The non-mucosal layer of traditional cookware has defects such as low hardness and no wear resistance, high temperature and easy decomposition, and the volatility of chemical coatings during the preparation process leads to environmental pollution.
The corrosion-resistant layer and non-stick layer are used to form a composite structure. The corrosion-resistant layer is made of copper oxide, alumina, silver oxide and other materials, with high thermal conductivity and corrosion resistance; the non-stick layer is high in aluminum oxide, titanium oxide, silicon carbide, etc. The hardness ceramic powder is made of, and the concave and convex surface with certain pores is formed by powder spraying, which improves the wear resistance of the non-stick layer and the non-stickness of the oil storage.
The non-stick composite layer is achieved with high thermal conductivity, corrosion resistance, wear resistance and oil storage non-stickness, avoiding the defects of the traditional non-mucosal layer and reducing environmental pollution.
Smart Images

Figure BDA0004408357660000131 
Figure BDA0004408357660000141
Abstract
Description
[Technical field]
[0001] The present application relates to the technical field of cookware, and in particular to a cooking utensil and a preparation method thereof. [Background technology]
[0002] In the traditional cookware industry, in order to ensure that the cookware has non-stick properties, non-stick chemical coatings are usually sprayed on the surface of the pot to form a non-stick film layer. The above-mentioned chemical coatings are mainly made of fluorocarbon resin and silica sol as raw materials. The chemical coatings will evaporate during the film making process, which poses obvious environmental pollution problems. In addition, the prepared non-stick film layer has defects such as low hardness, poor wear resistance, high temperature resistance and easy decomposition. Therefore, finding a new material and its processing technology that can replace conventional chemical coatings for use in cooking utensils has become a technical challenge in the industry. [Summary of the invention]
[0003] In view of this, the present application provides a cooking utensil and a preparation method thereof, wherein a non-stick composite layer is formed on the cooking utensil by selecting components and coordinating preparation methods, wherein the corrosion-resistant layer plays a role of heat conduction and corrosion resistance, and the non-stick layer plays a role of wear resistance and oil storage and non-stickiness.
[0004] In a first aspect, the present application provides a cooking utensil, the cooking utensil comprising a pot body and a non-stick composite layer, the non-stick composite layer comprising:
[0005] A corrosion-resistant layer is provided on at least a portion of the inner surface of the pot body; the components of the corrosion-resistant layer include but are not limited to one or more of copper oxide and its alloys, aluminum oxide and its alloys, silver oxide and its alloys;
[0006] The non-stick layer is arranged on at least a portion of the surface of the corrosion-resistant layer away from the pot body; the components of the non-stick layer include but are not limited to one or more of aluminum oxide and its composite materials, titanium oxide and its composite materials, silicon carbide and its composite materials, boron carbide and its composite materials, titanium nitride and its composite materials, chromium nitride and its composite materials, molybdenum nitride and its composite materials, and aluminum nitride and its composite materials.
[0007] In the above scheme, copper, aluminum, silver and their alloys have high thermal conductivity, and copper oxide, aluminum oxide, silver oxide and their alloys formed by heat treatment also have excellent corrosion resistance, so the corrosion-resistant layer obtained has the characteristics of high thermal conductivity and high corrosion resistance; the materials used for the non-stick layer are all high-hardness and corrosion-resistant ceramic powders. After spraying by powder spraying, a concave-convex surface with certain pores can be formed on at least part of the surface of the corrosion-resistant layer as a non-stick layer, so that the non-stick layer has both wear resistance and oil storage non-stickiness; at the same time, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer, and the non-stick layer serves as the surface layer of the non-stick composite layer. The non-stick layer is connected to the pot body through the corrosion-resistant layer. This connection method can improve the bonding force between the non-stick layer and the pot body.
[0008] In combination with the first aspect, the thickness of the corrosion-resistant layer is 30 μm to 100 μm.
[0009] In the above scheme, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer. If the thickness of the corrosion-resistant layer is too thick, the preparation cost of the non-stick composite layer will increase accordingly; if the thickness of the corrosion-resistant layer is too thin, the corrosion-resistant layer will be easily damaged during the use of the cooking utensil, thereby reducing the corrosion resistance of the cooking utensil and shortening the service life of the cooking utensil.
[0010] In combination with the first aspect, the porosity of the corrosion-resistant layer is 0% to 5%.
[0011] In the above scheme, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer. If the porosity of the corrosion-resistant layer is too high, the corrosive medium can easily pass through the corrosion-resistant layer and contact the pot body during the use of the cooking utensil, causing the pot body to be corroded.
[0012] In combination with the first aspect, the thermal conductivity of the corrosion-resistant layer is 230 W / m·K to 430 W / m·K.
[0013] In the above scheme, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer. If the thermal conductivity of the corrosion-resistant layer is too low, the heat transfer effect of the cooking utensil will be poor during use, and food will easily burn; if the thermal conductivity of the corrosion-resistant layer is too high, the preparation cost of the non-stick composite layer will be high.
[0014] In combination with the first aspect, the thickness of the non-stick layer is 30 μm to 100 μm.
[0015] In the above scheme, the non-stick layer serves as a non-stick functional layer of the non-stick composite layer. If the thickness of the non-stick layer is too thick, the preparation cost of the non-stick composite layer will increase accordingly; if the thickness of the non-stick layer is too thin, the non-stick layer is easily damaged by a spatula or the like during the use of the cooking utensil, thereby reducing the non-stick performance of the cooking utensil and thereby shortening the service life of the cooking utensil.
[0016] In combination with the first aspect, the porosity of the non-stick layer is 5% to 15%.
[0017] In the above scheme, the non-stick layer serves as a non-stick functional layer of the non-stick composite layer. If the porosity of the non-stick layer is too high, food is easily retained in the pores, affecting the use of the cooking utensils; if the porosity of the non-stick layer is too low, the non-stick layer is difficult to achieve the effect of oil storage and non-stickiness, thereby affecting the non-stick performance of the cooking utensils.
[0018] In combination with the first aspect, the hardness of the non-stick layer is 600 HV to 1200 HV.
[0019] In the above scheme, the non-stick layer serves as a non-stick functional layer of the non-stick composite layer. If the hardness of the non-stick layer is too low, the wear resistance of the non-stick layer will decrease and be damaged, and the non-stick effect of the cooking utensil will be reduced; if the hardness of the non-stick layer is too high, the preparation cost of the non-stick composite layer will be high.
[0020] In combination with the first aspect, the high temperature discoloration resistance temperature of the non-stick layer is 400°C to 500°C.
[0021] In the above scheme,
[0022] In a second aspect, the present application provides a method for preparing a cooking utensil, the method comprising:
[0023] Pre-treating at least a portion of the inner surface of the rough cooker blank to obtain a pot body;
[0024] Forming a base layer on at least a portion of the inner surface of the pot body using one or more of thermal spraying, physical vapor deposition, chemical electroplating or mechanical extrusion composite of a first powder material; wherein the first powder material includes but is not limited to one or more of copper powder and its alloy powder, aluminum powder and its alloy powder, silver powder and its alloy powder;
[0025] A second powder material is applied by powder spraying to form a non-stick layer on at least a portion of the surface of the base layer away from the pot body; wherein the second powder material includes but is not limited to one or more of aluminum oxide powder and composite powders thereof, titanium oxide powder and composite powders thereof, silicon carbide powder and composite powders thereof, boron carbide powder and composite powders thereof, titanium nitride powder and composite powders thereof, chromium nitride powder and composite powders thereof, molybdenum nitride powder and composite powders thereof, and aluminum nitride powder and composite powders thereof;
[0026] The pot body is calcined, and the base layer is converted into a corrosion-resistant layer to obtain a cooking utensil; wherein the components of the corrosion-resistant layer include but are not limited to one or more of copper oxide and its alloys, aluminum oxide and its alloys, and silver oxide and its alloys.
[0027] In the above scheme, copper, aluminum, silver and their alloys have high thermal conductivity, and copper oxide, aluminum oxide, silver oxide and their alloys formed by heat treatment also have excellent corrosion resistance, so the corrosion-resistant layer obtained has the characteristics of high thermal conductivity and high corrosion resistance; the materials used for the non-stick layer are all high-hardness and corrosion-resistant ceramic powders. After spraying by powder spraying, a concave-convex surface with certain pores can be formed on at least part of the surface of the corrosion-resistant layer as a non-stick layer, so that the non-stick layer has both wear resistance and oil storage non-stickiness; at the same time, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer, and the non-stick layer serves as the surface layer of the non-stick composite layer. The non-stick layer is connected to the pot body through the corrosion-resistant layer. This connection method can improve the bonding force between the non-stick layer and the pot body.
[0028] In combination with the second aspect, the particle size of the first powder material is 100 mesh to 300 mesh.
[0029] In the above scheme, if the particle size of the first powder material is too large, the surface of the prepared corrosion-resistant layer is too rough, resulting in too much material of the second powder material embedded in the troughs of the corrosion-resistant layer during the preparation of the non-stick layer, resulting in increased preparation costs of the non-stick composite layer; if the particle size of the first powder material is too small, the surface of the prepared corrosion-resistant layer is too smooth, which will reduce the bonding strength between the non-stick layer and the corrosion-resistant layer, causing the non-stick layer to easily fall off during use.
[0030] In combination with the second aspect, the particle size of the second powder material is 100 mesh to 300 mesh.
[0031] In the above scheme, if the particle size of the second powder material is too large, the surface of the prepared non-stick layer will be too rough, which will reduce the non-stick effect of the non-stick layer; if the particle size of the second powder material is too small, the preparation of the non-stick layer will result in too much second powder material embedded in the troughs of the corrosion-resistant layer, resulting in increased preparation costs for the non-stick composite layer.
[0032] In combination with the second aspect, the pretreatment process includes one or more of deburring, trimming, degreasing, mechanical sandblasting, polishing, and sandblasting.
[0033] In the above scheme, the above pretreatment process is used to eliminate defects such as protrusions on the surface of the pot body, thereby preventing the protrusions and other defects from affecting the adhesion effect of the subsequent non-stick layer and the corrosion-resistant layer.
[0034] In combination with the second aspect, the calcination temperature is 400°C to 500°C.
[0035] In the above scheme, if the calcination temperature is too high, it will not promote the oxidation process of the base layer, resulting in heat waste and increased preparation cost of the non-stick composite layer; if the calcination temperature is too low, the exposed elemental metal in the base layer cannot be completely converted into metal oxide, thereby reducing the corrosion resistance of the corrosion-resistant layer.
[0036] In combination with the second aspect, the calcination time is 5 minutes to 30 minutes.
[0037] In the above scheme, if the calcination time is too long, it will not promote the oxidation process of the base layer, resulting in heat waste and increased preparation cost of the non-stick composite layer; if the calcination time is too short, the exposed elemental metal in the base layer cannot be completely converted into metal oxide, thereby reducing the corrosion resistance of the corrosion-resistant layer.
[0038] In combination with the second aspect, the thickness of the corrosion-resistant layer is 30 μm to 100 μm.
[0039] In the above scheme, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer. If the thickness of the corrosion-resistant layer is too thick, the preparation cost of the non-stick composite layer will increase accordingly; if the thickness of the corrosion-resistant layer is too thin, the corrosion-resistant layer will be easily damaged during the use of the cooking utensil, thereby reducing the corrosion resistance of the cooking utensil and shortening the service life of the cooking utensil.
[0040] In combination with the second aspect, the porosity of the corrosion-resistant layer is 0% to 5%.
[0041] In the above scheme, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer. If the porosity of the corrosion-resistant layer is too high, the corrosive medium can easily pass through the corrosion-resistant layer and contact the pot body during the use of the cooking utensil, causing the pot body to be corroded.
[0042] In combination with the second aspect, the thermal conductivity of the corrosion-resistant layer is 230 W / m·K to 430 W / m·K.
[0043] In the above scheme, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer. If the thermal conductivity of the corrosion-resistant layer is too low, the heat transfer effect of the cooking utensil will be poor during use, and food will easily burn; if the thermal conductivity of the corrosion-resistant layer is too high, the preparation cost of the non-stick composite layer will be high.
[0044] In combination with the second aspect, the thickness of the non-stick layer is 30 μm to 100 μm.
[0045] In the above scheme, the non-stick layer serves as a non-stick functional layer of the non-stick composite layer. If the thickness of the non-stick layer is too thick, the preparation cost of the non-stick composite layer will increase accordingly; if the thickness of the non-stick layer is too thin, the non-stick layer is easily damaged by a spatula or the like during the use of the cooking utensil, thereby reducing the non-stick performance of the cooking utensil and thereby shortening the service life of the cooking utensil.
[0046] In combination with the second aspect, the porosity of the non-stick layer is 5% to 15%.
[0047] In the above scheme, the non-stick layer serves as a non-stick functional layer of the non-stick composite layer. If the porosity of the non-stick layer is too high, food is easily retained in the pores, affecting the use of the cooking utensils; if the porosity of the non-stick layer is too low, the non-stick layer is difficult to achieve the effect of oil storage and non-stickiness, thereby affecting the non-stick performance of the cooking utensils.
[0048] In combination with the second aspect, the hardness of the non-stick layer is 600 HV to 1200 HV.
[0049] In the above scheme, the non-stick layer serves as a non-stick functional layer of the non-stick composite layer. If the hardness of the non-stick layer is too low, the wear resistance of the non-stick layer will decrease and be damaged, and the non-stick effect of the cooking utensil will be reduced; if the hardness of the non-stick layer is too high, the preparation cost of the non-stick composite layer will be high.
[0050] In combination with the second aspect, the high temperature discoloration resistance temperature of the non-stick layer is 400°C to 500°C
[0051] In the above scheme, [Specific implementation method]
[0052] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0053] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0054] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0055] In the traditional cookware industry, in order to ensure that the cookware is non-stick, non-stick chemical coatings are usually sprayed on the surface of the pot to form a non-stick film layer. The above-mentioned chemical coatings are mainly made of fluorocarbon resin and silica sol as raw materials. The chemical coatings will evaporate during the film making process, which poses obvious environmental pollution problems. In addition, the prepared non-stick film layer has defects such as low hardness, poor wear resistance, high temperature resistance and easy decomposition.
[0056] In order to solve the defects of the above-mentioned non-stick film layer, the prior art adopts methods such as thermal spraying or physical vapor deposition, and uses metal materials or ceramic materials as raw materials, melts the metal materials or ceramic materials and deposits them on the surface of the substrate (such as the surface of an aluminum alloy substrate, a stainless steel substrate, a titanium alloy substrate, a cast iron substrate, etc.) to form a non-stick film layer with a metal layer as the bottom layer and a ceramic layer as the surface layer. In terms of material usage, the thermal spraying method usually uses corrosion-resistant titanium alloys and stainless steel as the bottom layer, and uses aluminum oxide, titanium oxide, molybdenum nitride, silicon carbide, boron carbide and their composite materials as the surface layer; physical vapor deposition or chemical plating (including electrochemical plating) generally uses chromium alloys as the bottom layer, and uses titanium nitride, chromium nitride, molybdenum nitride, aluminum nitride and their composite materials as the surface layer.
[0057] The non-stick film layer prepared by the above-mentioned thermal spraying or physical vapor deposition method, the bottom layer is used to provide bonding strength (currently mainly titanium alloy, stainless steel and chromium, which have good corrosion resistance), and the surface layer is used to provide high hardness and shovel resistance. Among them, the non-stick film layer formed by thermal spraying in combination with the above-mentioned materials needs to have a certain porosity to ensure that the non-stick film layer has the function of oil storage and non-stick, but the high-porosity corrosive liquid is easy to penetrate, resulting in galvanic corrosion between the substrate and the bottom layer, making the cooking utensils have problems such as insufficient corrosion resistance; the non-stick film layer formed by physical vapor deposition or chemical electroplating in combination with the above-mentioned materials has high hardness and good corrosion resistance, but has the problems of too high density, too low porosity, and no oil storage and non-stick function.
[0058] Therefore, finding a new film layer that can replace the conventional non-stick film layer and its processing technology has become a technical problem to be solved in the industry.
[0059] In view of this, the present application provides a cooking utensil, the cooking utensil comprising a pot body and a non-stick composite layer, the non-stick composite layer comprising:
[0060] The corrosion-resistant layer is disposed on at least part of the inner surface of the pot body; the components of the corrosion-resistant layer include but are not limited to one or more of copper oxide and its alloys, aluminum oxide and its alloys, silver oxide and its alloys;
[0061] The non-stick layer is arranged on at least a portion of the surface of the corrosion-resistant layer away from the pot body; the components of the non-stick layer include but are not limited to one or more of aluminum oxide and its composite materials, titanium oxide and its composite materials, silicon carbide and its composite materials, boron carbide and its composite materials, titanium nitride and its composite materials, chromium nitride and its composite materials, molybdenum nitride and its composite materials, and aluminum nitride and its composite materials.
[0062] In the above scheme, copper, aluminum, silver and their alloys have high thermal conductivity, and copper oxide, aluminum oxide, silver oxide and their alloys formed by copper, aluminum, silver and their alloys after heat treatment also have excellent corrosion resistance, so the corrosion-resistant layer obtained has the characteristics of high thermal conductivity and high corrosion resistance; the materials used for the non-stick layer are all high-hardness and corrosion-resistant ceramic powders. After spraying by powder spraying, a concave-convex surface with certain pores can be formed on at least part of the surface of the corrosion-resistant layer as a non-stick layer, so that the non-stick layer has both wear resistance and oil storage non-stickiness; at the same time, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer, and the non-stick layer serves as the surface layer of the non-stick composite layer. The non-stick layer is connected to the pot body through the corrosion-resistant layer. This connection method can improve the bonding force between the non-stick layer and the pot body.
[0063] In some embodiments, the corrosion-resistant layer used in the present application serves as an intermediate connecting layer between the non-stick layer and the pot body. Optionally, the corrosion-resistant layer can be arranged at the bottom area of the inner surface of the pot body, or can be arranged on the entire inner surface of the pot body. It can be selected according to actual needs and is not limited here. Preferably, the corrosion-resistant layer of the present application is arranged on the entire inner surface of the pot body.
[0064] The components of the corrosion-resistant layer include, but are not limited to, one or more of copper oxide and its alloys, aluminum oxide and its alloys, and silver oxide and its alloys, that is, the composition of the corrosion-resistant layer may include only one metal oxide or metal oxide alloy, or may include two or more metal oxides or metal oxide alloys. Exemplarily, the composition of the corrosion-resistant layer may be one of copper oxide, aluminum oxide, and silver oxide, or may be a combination of copper oxide and aluminum oxide, a combination of aluminum oxide and silver oxide, or a combination of aluminum oxide and its alloys, etc. The components of the corrosion-resistant layer may be selected according to actual needs, and are not limited here.
[0065] Among the components of the above-mentioned corrosion-resistant layer, copper, aluminum, silver and their alloys have high thermal conductivity, and copper oxide, aluminum oxide, silver oxide and their alloys formed by copper, aluminum, silver and their alloys after heat treatment also have excellent corrosion resistance. Therefore, the obtained corrosion-resistant layer has the characteristics of both high thermal conductivity and high corrosion resistance.
[0066] The thickness of the corrosion-resistant layer used in the present application is 30 μm to 100 μm. Optionally, the thickness of the corrosion-resistant layer can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. If the thickness of the corrosion-resistant layer is too thick, the required preparation materials and preparation difficulty will increase, so that the preparation cost of the cooking utensil will increase accordingly, and the thickness will reduce the thermal conductivity of the corrosion-resistant layer; if the thickness of the corrosion-resistant layer is too thin, the corrosion-resistant layer is easily damaged during the use of the cooking utensil, causing the corrosive medium to pass through the corrosion-resistant layer and contact the pot body, reducing the corrosion resistance of the cooking utensil, and thus shortening the service life of the cooking utensil.
[0067] The porosity of the corrosion-resistant layer is 0% to 5%. Optionally, the porosity of the corrosion-resistant layer can be 0%, 1%, 2%, 3%, 4%, 5%, etc., or other values within the range. It can be selected according to actual needs and is not limited here. The porosity of the corrosion-resistant layer is the ratio of the pores inside the corrosion-resistant layer to the total volume of the corrosion-resistant layer, that is, the structural density of the corrosion-resistant layer. If the porosity of the corrosion-resistant layer is too high, the corrosive medium can easily pass through the corrosion-resistant layer and contact the pot body during the use of the cooking utensil, causing the pot body to be corroded.
[0068] The thermal conductivity of the corrosion-resistant layer is 230W / m·K to 430W / m·K. Optionally, the thermal conductivity of the corrosion-resistant layer can be 230W / m·K, 300W / m·K, 330W / m·K, 360W / m·K, 380W / m·K, 400W / m·K, 430W / m·K, etc. It can also be other values within the range. It can be selected according to actual needs and is not limited here. The thermal conductivity of the corrosion-resistant layer refers to the inherent ability of the corrosion-resistant layer to transfer or conduct heat. If the thermal conductivity of the corrosion-resistant layer is too low, the heat transfer effect of the cooking utensil during use is poor, the temperature of each part of the cooking utensil is uneven, and the food is prone to coking; if the thermal conductivity of the corrosion-resistant layer is too high, the difficulty of preparation increases, and the preparation cost of the cooking utensil is high.
[0069] In some embodiments, the non-stick layer is disposed on at least a portion of the surface of the corrosion-resistant layer away from the pot body. Optionally, the non-stick layer can be disposed on the bottom area of the corrosion-resistant layer away from the pot body, or can be disposed on the entire inner surface of the corrosion-resistant layer away from the pot body. The selection can be made according to actual needs and is not limited here. Preferably, the non-stick layer of the present application is disposed on the entire inner surface of the corrosion-resistant layer away from the pot body.
[0070] The components of the non-stick layer include, but are not limited to, one or more of aluminum oxide and its composite materials, titanium oxide and its composite materials, silicon carbide and its composite materials, boron carbide and its composite materials, titanium nitride and its composite materials, chromium nitride and its composite materials, molybdenum nitride and its composite materials, and aluminum nitride and its composite materials. That is, the composition of the non-stick layer may include only one substance or its composite material, or may include two or more substances or their composite materials. Exemplarily, the composition of the non-stick layer may be one of aluminum oxide, titanium oxide, silicon carbide, boron carbide, titanium nitride, chromium nitride, molybdenum nitride, and aluminum nitride, or may be a combination of aluminum oxide and titanium oxide, a combination of titanium oxide and silicon carbide, or titanium oxide and its composite materials, etc. The components of the non-stick layer may be selected according to actual needs, and are not limited here.
[0071] Among the components of the above-mentioned non-stick layer, the materials used for the non-stick layer are all high-hardness and corrosion-resistant ceramic powders. After spraying by powder spraying, a concave-convex surface with certain pores can be formed on at least part of the surface of the corrosion-resistant layer as a non-stick layer, so that the non-stick layer has both wear resistance and oil storage non-stickiness.
[0072] The thickness of the non-stick layer used in the present application is 30 μm to 100 μm. Optionally, the thickness of the non-stick layer can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. If the thickness of the non-stick layer is too thick, the required preparation materials and preparation difficulty will increase, so that the preparation cost of the cooking utensil will increase accordingly; if the thickness of the non-stick layer is too thin, the non-stick layer is easily damaged by a spatula during the use of the cooking utensil, which reduces the non-stick performance of the cooking utensil and shortens the service life of the cooking utensil.
[0073] The porosity of the non-stick layer is 5% to 15%. Optionally, the porosity of the non-stick layer can be 5%, 8%, 10%, 13%, 15%, etc., or other values within the range. It can be selected according to actual needs and is not limited here. The porosity of the non-stick layer is the ratio of the pores inside the non-stick layer to the total volume of the non-stick layer, that is, the structural density of the non-stick layer. If the porosity of the non-stick layer is too high, food is easily left in the pores during the use of the cooking utensil, affecting the use of the cooking utensil; if the porosity of the non-stick layer is too low, it is difficult for the non-stick layer to achieve the effect of oil storage and non-stick, thereby affecting the non-stick performance of the cooking utensil.
[0074] The hardness of the non-stick layer is 600HV to 1200HV. Optionally, the hardness of the non-stick layer can be 600HV, 650HV, 700HV, 800HV, 900HV, 1000HV, 1100HV, 1200HV, etc. It can also be other values within the range. It can be selected according to actual needs and is not limited here. The hardness of the non-stick layer is the ability of the non-stick layer to resist external force pressing into the surface. Under the same external force, the non-stick layer with high hardness can be pressed into a shallow depth, so the hardness will affect the wear resistance of the non-stick layer. If the hardness of the non-stick layer is too low, the wear resistance of the non-stick layer will decrease, and the non-stick layer of the cooking utensils will be easily damaged during use, resulting in the failure of the non-stick effect of the cooking utensils; if the hardness of the non-stick layer is too high, the difficulty of preparation increases, so that the preparation cost of the cooking utensils will increase accordingly.
[0075] The high temperature discoloration temperature of the non-stick layer is 400℃~500℃. Optionally, the high temperature discoloration temperature of the non-stick layer can be 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, etc. It can also be other values within the range. It can be selected according to actual needs and is not limited here. High temperature discoloration refers to the oxidation of oxygen in the air and the surface of the non-stick layer to form oxides or oxide films during the use of cooking utensils, which changes color under high temperature conditions. If the high temperature discoloration temperature of the non-stick layer is too low, the non-stick layer will change color at a lower temperature, which will affect the aesthetics of the cooking utensils. If the high temperature discoloration temperature of the non-stick layer is too high, the difficulty of making the non-stick layer will increase, and the preparation cost of the cooking utensils will increase.
[0076] In some embodiments, the non-stick composite layer having both heat conductivity and corrosion resistance, wear resistance and oil storage non-stick properties is prepared by the following steps:
[0077] Step S10, pre-treating at least a portion of the inner surface of the rough cooker blank to obtain a cooker body;
[0078] Step S20, forming a base layer on at least a portion of the inner surface of the pot body by using one or more of thermal spraying, physical vapor deposition, chemical plating or mechanical extrusion composite to form a first powder material; wherein the first powder material includes but is not limited to one or more of copper powder and its alloy powder, aluminum powder and its alloy powder, silver powder and its alloy powder;
[0079] Step S30, using a second powder material to form a non-stick layer on at least a portion of the surface of the base layer away from the pot body by powder spraying; wherein the second powder material includes but is not limited to one or more of aluminum oxide powder and composite powders thereof, titanium oxide powder and composite powders thereof, silicon carbide powder and composite powders thereof, boron carbide powder and composite powders thereof, titanium nitride powder and composite powders thereof, chromium nitride powder and composite powders thereof, molybdenum nitride powder and composite powders thereof, and aluminum nitride powder and composite powders thereof;
[0080] Step S40, calcining the pot body, converting the base layer into a corrosion-resistant layer, and obtaining a cooking utensil; wherein the components of the corrosion-resistant layer include but are not limited to one or more of copper oxide and its alloys, aluminum oxide and its alloys, and silver oxide and its alloys.
[0081] In the above scheme, the composition and attachment method of the first powder material make the prepared corrosion-resistant layer have high thermal conductivity and low porosity, so that the corrosion-resistant layer has the characteristics of high thermal conductivity and corrosion resistance; the composition and attachment method of the second powder material make it have high hardness and a certain porosity, so that the non-stick layer has the characteristics of wear resistance and oil storage and non-stickiness; at the same time, the corrosion-resistant layer serves as the bottom layer of the non-stick composite layer, the non-stick layer serves as the surface layer of the non-stick composite layer, and the non-stick layer is connected to the pot body through the corrosion-resistant layer. This connection method can improve the bonding strength between the non-stick layer and the pot body.
[0082] Before step S10, the preparation method also includes preparing a cooker blank with a cooking cavity from a pot body substrate such as stainless steel through stretching, spinning, extrusion, cutting and other processing techniques, and the thickness and size of the cooker blank can be adjusted according to actual needs and are not limited here.
[0083] In step S10, the processed and formed cookware rough blank cannot be used directly, and there will be defects such as burrs on the surface, which need to be eliminated by a pretreatment process. The pretreatment process of the present application includes one or more of deburring, trimming, degreasing, mechanical sandblasting, polishing, and sandblasting. Degreasing refers to removing oil stains on the surface of the pot body to prevent the oil stains from affecting the bonding force between the non-stick composite layer and the pot body; mechanical sandblasting or sandblasting can remove rust and other dirt on the surface of the pot body, and form a pot body surface with a certain degree of roughness to enhance the bonding force between the non-stick composite layer and the pot body; polishing can improve the smoothness of the pot body surface to obtain a smooth surface and increase the gloss effect. It can be understood that through the above-mentioned pretreatment process, defects such as protrusions on the surface of the pot body can be eliminated to prevent defects such as protrusions from affecting the adhesion effect of the subsequent non-stick layer and the corrosion-resistant layer, thereby improving the connection stability between the non-stick composite layer and the pot body.
[0084] In step S20, the base layer can be disposed in the bottom area of the inner surface of the pot body, or can be disposed on the entire inner surface of the pot body, which can be selected according to actual needs and is not limited here; preferably, the base layer of the present application is disposed on the entire inner surface of the pot body. Specifically, in step S20, one or more first materials such as copper powder and its alloy powder, aluminum powder and its alloy powder, silver powder and its alloy powder are formed into a base layer on at least part of the inner surface of the pot body by thermal spraying, physical vapor deposition, chemical electroplating or mechanical extrusion compounding. Among them, thermal spraying is to spray the first powder material in a molten state onto the inner surface of the pot body through a high-speed airflow to form a base layer. Moreover, compared with physical vapor deposition, chemical plating or mechanical extrusion composite, thermal spraying can use dispersion strengthening to strengthen the base layer, improve the hardness of the base layer, and increase the scratch resistance. Physical vapor deposition refers to the use of physical methods to vaporize the first powder material source into gaseous atoms, molecules or partially ionized into ions under vacuum conditions, and deposit it on the surface of the pot body through low-pressure gas (or plasma) to form a base layer. Chemical plating is based on the principle of redox reaction, using a strengthening reducing agent in a solution containing the required metal ions to reduce metal ions into metals (i.e., the metal contained in the first powder material) and deposit them on the surface of the pot body to form a base layer. Mechanical extrusion composite refers to extruding the first powder material into a film on the inner surface of the pot body. The film-forming method of the base layer can be selected according to actual needs, and is not limited here.
[0085] In the selection of the above-mentioned first powder material, the first powder material can select only one metal or metal alloy, or it can include two or more metals or metal alloys. Exemplarily, the composition of the first powder material can be one of copper, aluminum, and silver, or it can be a combination of copper and aluminum, a combination of aluminum and silver, or a combination of aluminum and its alloys, etc. The first powder material can be selected according to actual needs and is not limited here.
[0086] The particle size of the first powder material used in this application is 100 mesh to 300 mesh. Optionally, the particle size of the first powder material can be 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, etc., or other values within the range. It can be selected according to actual needs and is not limited here. If the particle size of the first powder material is too large, the surface roughness of the prepared corrosion-resistant layer is too large. When the second powder material is used to prepare the non-stick layer later, the number of the second powder material embedded in the trough (i.e., the concave part between adjacent powder particles) of the corrosion-resistant layer is too large, and the amount of the second powder material used increases, thereby increasing the preparation cost of the cooking utensil; if the particle size of the first powder material is too small, the surface of the prepared corrosion-resistant layer is too smooth. When the non-stick layer is prepared, the bonding force between the non-stick layer and the corrosion-resistant layer is insufficient, that is, the bonding strength between the non-stick layer and the corrosion-resistant layer is reduced, resulting in the non-stick layer being easy to fall off during use, affecting the use of the cooking utensil.
[0087] In step S30, the non-stick layer can be arranged at the bottom area of the base layer away from the pot body, or can be arranged at the entire inner surface of the base layer away from the pot body, which can be selected according to actual needs and is not limited here; preferably, the non-stick layer of the present application is arranged at the entire inner surface of the base layer away from the pot body. Specifically, in step S30, a second powder material such as one or more of aluminum oxide powder and its composite material powder, titanium oxide powder and its composite material powder, silicon carbide powder and its composite material powder, boron carbide powder and its composite material powder, titanium nitride powder and its composite material powder, chromium nitride powder and its composite material powder, molybdenum nitride powder and its composite material powder, aluminum nitride powder and its composite material powder is formed into a non-stick layer on at least part of the surface of the base layer by powder spraying or the like. Powder spraying is to spray the second powder material onto the surface of the base layer with a powder spraying device. Under the action of static electricity, the second powder material will be uniformly adsorbed on the surface of the base layer to form a powdery non-stick layer.
[0088] In the selection of the second powder material, the second powder material may be selected from only one substance or a composite material thereof, or may include two or more substances or a composite material thereof. Exemplarily, the second powder material may be one of aluminum oxide, titanium oxide, silicon carbide, boron carbide, titanium nitride, chromium nitride, molybdenum nitride, and aluminum nitride, or may be a combination of aluminum oxide and titanium oxide, a combination of titanium oxide and silicon carbide, or titanium oxide and a composite material thereof, etc. The second powder material may be selected according to actual needs, and is not limited here.
[0089] The particle size of the second powder material used in this application is 100 mesh to 300 mesh. Optionally, the particle size of the second powder material can be 100 mesh, 150 mesh, 200 mesh, 250 mesh, 300 mesh, etc., or other values within the range. It can be selected according to actual needs and is not limited here. If the particle size of the second powder material is too large, the surface roughness of the prepared non-stick layer is too large, which will reduce the non-stick effect of the non-stick layer; if the particle size of the second powder material is too small, when preparing the non-stick layer, the second powder material is embedded in the trough of the corrosion-resistant layer (i.e., the concave part between adjacent powder particles) too much, the amount of the second powder material used increases, and then the preparation cost of the cooking utensil is increased.
[0090] It should be noted that when the mesh number of the first powder material in this application is small, that is, the particle size of the first powder material is large, the prepared base layer has a large coarseness. Under this condition, the roughness of the base layer will also cause the non-stick layer prepared by the second powder material to have a large coarseness, so that the surface oil storage effect of the non-stick layer is good.
[0091] In step S40, the pot body needs to be calcined to allow the base layer to undergo an oxidation process. It is understandable that after high-temperature calcination, the exposed elemental metal in the base layer will be converted into its oxide, such as exposed copper into copper oxide, exposed silver into silver oxide, exposed aluminum into aluminum oxide, etc., thereby obtaining a corrosion-resistant layer with corrosion resistance.
[0092] Wherein, the calcination temperature is 400℃~500℃, and the calcination time is 5min~30min. Optionally, the calcination temperature can be 400℃, 410℃, 420℃, 430℃, 440℃, 450℃, 460℃, 470℃, 480℃, 490℃, 500℃, etc., and the calcination time can be 5min, 10min, 15min, 20min, 25min, 30min, etc., or other values within the range, which can be selected according to actual needs and are not limited here. If the calcination temperature is too high or the time is too long, it will not promote the oxidation process of the base layer, resulting in heat waste and increased preparation cost of the non-stick composite layer; if the calcination temperature is too low or the calcination time is too short, the exposed elemental metal in the base layer cannot be completely converted into metal oxide, thereby reducing the corrosion resistance of the corrosion-resistant layer.
[0093] After step S40, the process further includes step S50: performing a surface rolling and finishing process on the pot body. Specifically, the surface of the calcined product is polished, wax-sealed, etc. according to the appearance requirements to eliminate surface defects.
[0094] Through the above steps S10, S20, S30, S40 and S50, the cooking utensil of the present application having the effects of heat conduction, corrosion resistance, wear resistance and oil storage and non-stick can be obtained.
[0095] The thickness of the corrosion-resistant layer is 30μm to 100μm. Optionally, the thickness of the corrosion-resistant layer can be 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, etc. It can also be other values within the range. It can be selected according to actual needs and is not limited here. If the thickness of the corrosion-resistant layer is too thick, the required preparation materials and preparation difficulty will increase, so that the preparation cost of the cooking utensil will increase accordingly, and the thickness will reduce the thermal conductivity of the corrosion-resistant layer; if the thickness of the corrosion-resistant layer is too thin, the corrosion-resistant layer is easily damaged during the use of the cooking utensil, causing the corrosive medium to pass through the corrosion-resistant layer and contact the pot body, reducing the corrosion resistance of the cooking utensil, and thus shortening the service life of the cooking utensil.
[0096] The porosity of the corrosion-resistant layer is 0% to 5%. Optionally, the porosity of the corrosion-resistant layer can be 0%, 1%, 2%, 3%, 4%, 5%, etc., or other values within the range. It can be selected according to actual needs and is not limited here. The porosity of the corrosion-resistant layer is the ratio of the pores inside the corrosion-resistant layer to the total volume of the corrosion-resistant layer, that is, the structural density of the corrosion-resistant layer. If the porosity of the corrosion-resistant layer is too high, the corrosive medium can easily pass through the corrosion-resistant layer and contact the pot body during the use of the cooking utensil, causing the pot body to be corroded.
[0097] The thermal conductivity of the corrosion-resistant layer is 230W / m·K to 430W / m·K. Optionally, the thermal conductivity of the corrosion-resistant layer can be 230W / m·K, 300W / m·K, 330W / m·K, 360W / m·K, 380W / m·K, 400W / m·K, 430W / m·K, etc. It can also be other values within the range. It can be selected according to actual needs and is not limited here. The thermal conductivity of the corrosion-resistant layer refers to the inherent ability of the corrosion-resistant layer to transfer or conduct heat. If the thermal conductivity of the corrosion-resistant layer is too low, the heat transfer effect of the cooking utensil during use is poor, the temperature of each part of the cooking utensil is uneven, and the food is prone to coking; if the thermal conductivity of the corrosion-resistant layer is too high, the difficulty of preparation increases, and the preparation cost of the cooking utensil is high.
[0098] The thickness of the non-stick layer is 30 μm to 100 μm. Optionally, the thickness of the non-stick layer can be 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, etc., or other values within the range. It can be selected according to actual needs and is not limited here. If the thickness of the non-stick layer is too thick, the required preparation materials and preparation difficulty will increase, so that the preparation cost of the cooking utensil will increase accordingly; if the thickness of the non-stick layer is too thin, the non-stick layer is easily damaged by a spatula during the use of the cooking utensil, which reduces the non-stick performance of the cooking utensil and shortens the service life of the cooking utensil.
[0099] The porosity of the non-stick layer is 5% to 15%. Optionally, the porosity of the non-stick layer can be 5%, 8%, 10%, 13%, 15%, etc., or other values within the range. It can be selected according to actual needs and is not limited here. The porosity of the non-stick layer is the ratio of the pores inside the non-stick layer to the total volume of the non-stick layer, that is, the structural density of the non-stick layer. If the porosity of the non-stick layer is too high, food is easily left in the pores during the use of the cooking utensil, affecting the use of the cooking utensil; if the porosity of the non-stick layer is too low, it is difficult for the non-stick layer to achieve the effect of oil storage and non-stick, thereby affecting the non-stick performance of the cooking utensil.
[0100] The hardness of the non-stick layer is 600HV to 1200HV. Optionally, the hardness of the non-stick layer can be 600HV, 650HV, 700HV, 800HV, 900HV, 1000HV, 1100HV, 1200HV, etc. It can also be other values within the range. It can be selected according to actual needs and is not limited here. The hardness of the non-stick layer is the ability of the non-stick layer to resist external force pressing into the surface. Under the same external force, the non-stick layer with high hardness can be pressed into a shallow depth, so the hardness will affect the wear resistance of the non-stick layer; if the hardness of the non-stick layer is too low, the wear resistance of the non-stick layer will decrease, and the non-stick layer of the cooking utensils will be easily damaged during use, resulting in the failure of the non-stick effect of the cooking utensils; if the hardness of the non-stick layer is too high, the difficulty of preparation increases, so that the preparation cost of the cooking utensils will increase accordingly.
[0101] The following is a discussion with reference to specific embodiments.
[0102] Embodiment 1:
[0103] (1) deburring, trimming, degreasing, mechanically sandblasting, polishing, sandblasting, etc. are performed on at least a portion of the inner surface of the rough cookware to obtain a pot body;
[0104] (2) using a plasma spraying method to form a base layer with a thickness of 30 to 35 μm on the inner surface of the pot body with 100-mesh copper powder; wherein the voltage of the plasma spraying is 40 V and the current of the plasma spraying is 300 A;
[0105] (3) using a 100-mesh titanium oxide and aluminum oxide composite powder to form a non-stick layer with a thickness of 30 to 35 μm on the surface of the base layer by powder spraying; wherein the voltage of the powder spraying is 70 V and the current of the powder spraying is 600 A;
[0106] (4) The pot body is calcined at 400° C. for 5 min to convert the base layer into a corrosion-resistant layer, and the surface is modified to obtain a cooking utensil.
[0107] Embodiment 2:
[0108] The difference from Example 1 is that the particle size of the copper powder is 300 mesh, the spraying voltage is 30V, the spraying current is 250A, and the thickness of the base layer is 90-100 μm;
[0109] The calcination temperature is 450°C and the calcination time is 15 min.
[0110] Embodiment 3:
[0111] The difference from Example 1 is that the particle size of the titanium oxide and aluminum oxide composite powder is 300 mesh, the spraying voltage is 65V, the spraying current is 500A, and the thickness of the non-stick layer is 90-100μm;
[0112] The calcination temperature is 400°C and the calcination time is 30 min.
[0113] Embodiment 4:
[0114] The difference from Example 1 is that the particle size of the copper powder is 300 mesh, the spraying voltage is 30V, the spraying current is 250A, and the thickness of the base layer is 90-100 μm;
[0115] The particle size of the titanium oxide and aluminum oxide composite powder is 300 mesh, the spraying voltage is 65V, the spraying current is 500A, and the thickness of the non-stick layer is 90-100μm;
[0116] The calcination temperature is 500°C and the calcination time is 30 min.
[0117] Comparative Example 1:
[0118] The difference from Example 1 is that titanium powder is used to prepare the base layer.
[0119] Comparative Example 2:
[0120] The difference from Example 1 is that titanium powder is used to prepare the base layer, the particle size of the titanium powder is 300 mesh, the spraying voltage is 30V, the spraying current is 250A, and the thickness of the base layer is 90-100 μm.
[0121] Comparative Example 3:
[0122] The difference from Example 1 is that titanium powder is used to prepare the base layer, the particle size of the titanium oxide and aluminum oxide composite powder is 300 mesh, the spraying voltage is 65V, the spraying current is 500A, and the thickness of the non-stick layer is 90-100 μm.
[0123] Comparative Example 4:
[0124] The difference from Example 1 is that titanium powder is used to prepare the base layer, the particle size of the titanium powder is 300 mesh, the spraying voltage is 30V, the spraying current is 250A, and the thickness of the base layer is 90-100μm;
[0125] The particle size of the titanium oxide and aluminum oxide composite powder is 300 meshes, the spraying voltage is 65V, the spraying current is 500A, and the thickness of the non-stick layer is 90-100 μm.
[0126] Comparative Example 5:
[0127] Different from Example 1, this comparative example adopts a 304 stainless steel pot.
[0128]
[0129] test:
[0130] (1) Thickness measurement is to place the cross section of the product under a microscope to observe and measure the relevant thickness.
[0131] (2) The porosity is calculated and measured as (1-density after thermal spraying / density of raw material)*100%.
[0132] (3) Egg white carbonization temperature: Heat the cooking vessel to the test temperature, then pour 20±2g of egg white liquid into the cooking vessel positioned with a silicone ring. Keep warm for 2 minutes, and then evaluate whether the color of the egg white bottom layer is carbonized after solidification.
[0133] (4) The test method for oil storage non-stick is to heat the cooking utensil to 80-100℃, then pour cooking oil into it and wipe the cooking surface evenly with oil-absorbing paper. After heating to 220-260℃, wash it with cold water, and then continuously perform the egg non-stick test at the same position of the cooking utensil until the egg sticks to the pan, and record the relevant experimental data.
[0134] (5) The corrosion resistance test is carried out according to the national standard GB / T32388 for cookware products.
[0135] Test results:
[0136]
[0137] It should be noted that the high carbonization temperature of egg white means that the thermal conductivity of the corrosion-resistant layer is high, and thus the thermal conductivity of the cooking utensils is good, and food is not easy to stick to the pan, carbonize or burn (carbonization or burning of food will form carcinogens - such as acrylamide).
[0138] According to the test results of Example 2 and Example 1, as the particle size of the first powder material increases, the prepared corrosion-resistant layer has a large coarseness, and under this condition, the non-stick layer prepared by the second powder material will have a large coarseness and a high porosity, so that the surface oil storage effect of the non-stick layer is good, that is, the non-stick effect of the non-stick layer is good; and as the thickness of the corrosion-resistant layer increases, the corrosion-resistant effect of the corrosion-resistant layer is enhanced; at the same time, the first powder material is a high thermal conductivity material, and when the thickness of the corrosion-resistant layer is within the range of 30μm to 100μm, the thinner the thickness of the corrosion-resistant layer, the better the thermal conductivity of the cooking utensil.
[0139] According to the test results of Example 3 and Example 1, as the particle size of the second powder material increases, the non-stick layer prepared by the second powder material has a large coarseness and a high porosity, so that the surface oil storage effect of the non-stick layer is good, that is, the non-stick effect of the non-stick layer is good; and as the thickness of the non-stick layer decreases, the thermal conductivity of the cooking utensil is enhanced; at the same time, as the particle size of the second powder material decreases, the density of the non-stick layer increases, and the corrosion resistance of the cooking utensil is enhanced.
[0140] According to the test results of Example 4 and Example 1, as the particle sizes of the first powder material and the second powder material decrease, the non-stick effect of the cooking utensil decreases, but the corrosion resistance effect increases.
[0141] According to the test results of Examples 1 to 4 and Comparative Examples 1 to 5, it can be seen that compared with other existing materials, the copper, aluminum, silver and their alloys used in the present application have high thermal conductivity, and the copper oxide, aluminum oxide, silver oxide and their alloys formed by copper, aluminum, silver and their alloys after heat treatment also have excellent corrosion resistance. Therefore, the obtained corrosion-resistant layer has the characteristics of both high thermal conductivity and high corrosion resistance compared with other film layers in the prior art.
[0142] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A cooking utensil, characterized in that: The cooking utensil comprises a pot body and a non-stick composite layer, wherein the non-stick composite layer comprises: A corrosion-resistant layer is provided on at least a portion of the inner surface of the pot body; the components of the corrosion-resistant layer include but are not limited to one or more of copper oxide and its alloys, aluminum oxide and its alloys, silver oxide and its alloys; The non-stick layer is arranged on at least a portion of the surface of the corrosion-resistant layer away from the pot body; the components of the non-stick layer include but are not limited to one or more of aluminum oxide and its composite materials, titanium oxide and its composite materials, silicon carbide and its composite materials, boron carbide and its composite materials, titanium nitride and its composite materials, chromium nitride and its composite materials, molybdenum nitride and its composite materials, and aluminum nitride and its composite materials.
2. The cooking device according to claim 1, characterized in that: The cooking appliance has at least one of the following features: (1) The thickness of the corrosion-resistant layer is 30 μm to 100 μm; (2) The porosity of the corrosion-resistant layer is 0% to 5%; (3) The thermal conductivity of the corrosion-resistant layer is 230 W / m·K to 430 W / m·K.
3. The cooking device according to claim 1, characterized in that: The cooking appliance has at least one of the following features: (1) The thickness of the non-stick layer is 30 μm to 100 μm; (2) The porosity of the non-stick layer is 5% to 15%; (3) The hardness of the non-stick layer is 600HV to 1200HV; (4) The high temperature discoloration resistance temperature of the non-stick layer is 400°C to 500°C.
4. A method for preparing a cooking utensil, characterized in that: The preparation method comprises: Pre-treating at least a portion of the inner surface of the rough cooker blank to obtain a pot body; Forming a base layer on at least a portion of the inner surface of the pot body using one or more of thermal spraying, physical vapor deposition, chemical electroplating or mechanical extrusion composite of a first powder material; wherein the first powder material includes but is not limited to one or more of copper powder and its alloy powder, aluminum powder and its alloy powder, silver powder and its alloy powder; A second powder material is applied by powder spraying to form a non-stick layer on at least a portion of the surface of the base layer away from the pot body; wherein the second powder material includes but is not limited to one or more of aluminum oxide powder and composite powders thereof, titanium oxide powder and composite powders thereof, silicon carbide powder and composite powders thereof, boron carbide powder and composite powders thereof, titanium nitride powder and composite powders thereof, chromium nitride powder and composite powders thereof, molybdenum nitride powder and composite powders thereof, and aluminum nitride powder and composite powders thereof; The pot body is calcined, and the base layer is converted into a corrosion-resistant layer to obtain a cooking utensil; wherein the components of the corrosion-resistant layer include but are not limited to one or more of copper oxide and its alloys, aluminum oxide and its alloys, and silver oxide and its alloys.
5. The preparation method according to claim 4, characterized in that: The preparation method has at least one of the following characteristics: (1) The particle size of the first powder material is 100 mesh to 300 mesh; (2) The particle size of the second powder material is 100 mesh to 300 mesh.
6. The preparation method according to claim 4, characterized in that: The pretreatment process includes one or more of deburring, trimming, degreasing, mechanical sandblasting, polishing, and sandblasting.
7. The preparation method according to claim 4, characterized in that: The preparation method has at least one of the following characteristics: (1) The calcination temperature is 400° C. to 500° C.; (2) The calcination time is 5 min to 30 min.
8. The preparation method according to claim 4, characterized in that: The preparation method has at least one of the following characteristics: (1) The thickness of the corrosion-resistant layer is 30 μm to 100 μm; (2) The porosity of the corrosion-resistant layer is 0% to 5%; (3) The thermal conductivity of the corrosion-resistant layer is 230 W / m·K to 430 W / m·K.
9. The preparation method according to claim 4, characterized in that: The preparation method has at least one of the following characteristics: (1) The thickness of the non-stick layer is 30 μm to 100 μm; (2) The porosity of the non-stick layer is 5% to 15%; (3) The hardness of the non-stick layer is 600HV to 1200HV; (4) The high temperature discoloration resistance temperature of the non-stick layer is 400°C to 500°C.